Bacterial nanotubes as a manifestation of cell death - Pospíšil, Jiří; Vítovská, Dragana; Kofroňová, Olga; Muchová, Katarína; Šanderová, Hana; Hubálek, Martin; Šiková, Michaela; Modrák, Martin; Benada, Oldřich; Barák, Imrich; Krásný, Libor (Nature communications, 2020)
Bacterial nanotubes are membranous structures that have been reported to function as conduits between cells to exchange DNA, proteins, and nutrients. Here, we investigate the morphology and formation of bacterial nanotubes using Bacillus subtilis. We show that nanotube formation is associated with stress conditions, and is highly sensitive to the cells' genetic background, growth phase, and sample preparation methods. Remarkably, nanotubes appear to be extruded exclusively from dying cells, likely as a result of biophysical forces. Their emergence is extremely fast, occurring within seconds by cannibalizing the cell membrane. Subsequent experiments reveal that cell-to-cell transfer of non-conjugative plasmids depends strictly on the competence system of the cell, and not on nanotube formation. Our study thus supports the notion that bacterial nanotubes are a post mortem phenomenon involved in cell disintegration, and are unlikely to be involved in cytoplasmic content exchange between live cells.
Keywords: Conjugation, Genetic; nanotrubičky; DNA bakterií; DNA, Bacterial; Nanotubes; Plasmids; Bacillus subtilis; plazmidy; mikrobiální viabilita; Microbial Viability; konjugace genetická